1977
DOI: 10.1177/00220345770560031301
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effects of 9-P-D-Arabinofuranosyladenine in a Mammalian Cell Line Devoid of Adenosine Deaminase Activity

Abstract: The effect of ara-A on cellular growth, DNA synthesis, and RNA synthesis, and RNA synthesis was measured in an established cell line (B-mix K-44/6) devoid of adenosine deaminase activity. Cells adapted to growth in a medium supplemented with horse serum provided an environment totally lacking adenosine deaminase activity whereas cultivation of cells in a medium supplemented with calf serum provided a system capable of deaminating ara-A to ara-H (half-life = 14 hours). Under deaminase-free conditions early log … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1978
1978
1985
1985

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…In addition, duplicate flasks without drug were held at 20C during the 12-hour incubation period to provide data on the amount of DNA present prior to the incubation period. After incubation, cells from all cultures were harvested and portions of suspended cells were assayed for cell number and incorporated [3HJthymidine by techniques described previously (5,17). The remainder of the cells were pelleted by centrifugation, lysed by resuspension in 0.1I percent sodium citrate containing propidium diiodide (50 RigIml), and examined in a Coulter model TPS-I flow cytometer according to the procedure of Krishan (18).…”
mentioning
confidence: 99%
“…In addition, duplicate flasks without drug were held at 20C during the 12-hour incubation period to provide data on the amount of DNA present prior to the incubation period. After incubation, cells from all cultures were harvested and portions of suspended cells were assayed for cell number and incorporated [3HJthymidine by techniques described previously (5,17). The remainder of the cells were pelleted by centrifugation, lysed by resuspension in 0.1I percent sodium citrate containing propidium diiodide (50 RigIml), and examined in a Coulter model TPS-I flow cytometer according to the procedure of Krishan (18).…”
mentioning
confidence: 99%
“…Adenosine deaminase was found and isolated as the enzyme which converts ara-A to ara-Hx (CORY and SUHADOLNIK 1965;FREDERIKSEN 1966;BLOCH et al 1967). DRACH et al (1977) also demonstrated that ara-A significantly inhibited cellular growth and DNA synthesis in adenosine deaminase-negative cell lines (B-mix K-44/6). They also showed that when adenosine deaminase-containing calf serum was added to the media, the cytotoxic effect of ara-A was almost reversed.…”
Section: Metabolism Distribution and Excretionmentioning
confidence: 99%
“…However, Whitely et al (30) have reported the successful control of biopsy-proven HSV encephalitis by systemic administration of ara-A. Topical application of antiviral agents has shown moderately successful results in the eye but less than satisfactory results on skin and mucocutaneous junctions (14,15 Recently, ara-AMP was synthesized to eliminate some of the disadvantages of ara-A, i.e., extremely low water solubility (24) and metabolic instability (1,5,24). Even though ara-AMP has been used successfully against HSV in vitro (26,28) and in animal models (15,17,27,28) the transport of ara-AMP across the cell membrane is highly limited because of its charged phosphate group.…”
mentioning
confidence: 99%